PREVALENCE, SOCIO-DEMOGRAPHIC DETERMINANTS AND RISK FACTORS OF TOXOPLASMOSIS: CASE-CONTROL STUDY IN A RURAL COMMUNITY OF MARDAN DISTRICT, NORTHERN PAKISTAN - M. N. K. Khattak; M. Iltaf; A. U. Rehman; S. Malik; M. Zahid (Journal of Animal and Plant Sciences, 2017)
Toxoplasmosis causes huge morbidity and mortality in variety of warm blooded hosts including humans. The present study aimed at establishing the prevalence, distributions and risk factors of toxoplasmosis in the human population of Mardan district, northern Pakistan. A retrospective case-control study was launched and 600 subjects (cases= 301, control= 299) were randomly enrolled from Mardan district. The cases had contact with domestic animals while controls had no contact. All the subjects were screened for seropositivity of Toxoplasma gondii specific antibodies using Latex Agglutination Test. Prevalence and the associated risk factors of toxoplasmosis were assessed through the standard procedures of descriptive statistics. In the total sample, the prevalence of toxoplasmosis was 178.3/1,000 (proportion 0.1783; 95% Confidence Interval (CI): 0.1477-0.2090). Prevalence in the control sample was 130.4/1,000. The prevalence of toxoplasmosis was significantly higher among the illiterate (Odds Ratio (OR): 1.84) and low income subjects (OR: 1.92) and had no association with gender, age and region. The prevalence of toxoplasmosis was substantially higher among the cases versus controls (OR: 1.95), and caused significantly higher numbers of abortions in women (OR: 6.00). Toxoplasmosis was higher among subjects who had cow/buffalo. Collectively, the enrolled cohort had poor knowledge about toxoplasmosis and undertook little or no preventive measures related to domestic animals. The prevalence of toxoplasmosis was comparatively higher in Mardan compared to the other regions of the province and had severe impact on the infected subjects. Better understanding of the socio-demographic differentials of infection could be helpful in decreasing the prevalence of this disease in the populations.
Keywords: Toxoplasmosis; Toxoplasma sp.; case-control study; Mardan; Pakistan